Strategies for Improving the Quality of Santri through Sufi Healing - Mu'azzaz, Nisrin; Rikza Chamami, M. (The Institute of Research and Service Community IPMAFA Pati, 2025)
Pesantren commits to providing quality educational services in the face of the times to produce quality santri. This study aims to explore the strategies implemented by Pesantren of Fathimah Al-Amin Progressive to improve the quality of its santri through Sufi Healing extracurricular. The research method used is qualitative with a case study approach. Data were collected through in-depth interviews with caregivers, coaches, coordinators, and santri and participant observation in Sufi Healing extracurricular activities. The results showed that Pesantren of Fathimah Al-Amin Progressive has succeeded in improving the quality of its santri through Sufi Healing extracurricular. This success is characterized by the ability of santri to overcome problems faced by themselves and others. The strategies to achieve this success include motivating santri about future opportunities, teaching practical values from Sufi Healing learning, and increasing practice rather than theory in their education. This research contributes to understanding practical pedagogical approaches within pesantren, particularly demonstrating how spiritual-based extracurricular activities can foster practical problem-solving skills and enhance santri well-being.